Efficacy and Prognostic Factors of Docetaxel Rechallenge on Metastatic Castration-resistant Prostate Cancer Patients - DUAN Liqun; ZHANG Qu; LIU Sanhe; DENG Kangli; WEI Shaozhong (Zhongliu Fangzhi Yanjiu, 2019)
Objective To assess the efficacy of docetaxel rechallenge on castration-resistant prostate cancer (mCRPC) patients and to analyze prognostic factors. Methods We retrospectively reviewed the medical history of 120 mCRPC patients treated with the first-line docetaxel chemotherapy effectively and progressed with docetaxel rechallenge. Coprimary end points were prostate specific antigen progression-free survival (PSA PFS) after the first sequence docetaxel chemotherapy, prostate specific antigen progression-free survival after docetaxel rechallenge (Rechallenge PSA PFS) and overall survival (OS). Univariable and multivariable Cox analyses were performed to determine prognostic factors associated with PSA PFS, Rechallenge PSA PFS and OS. Results At a median follow-up of 32.73 months, 30(25%) patients were still alive. The median PSA PFS, Rechallenge PSA PFS and OS were 13.89(7.67-39.00), 5.29(1.25-20.00) and 27.13(12.40-60.50) months, respectively. In multivariate analysis, treatment-free interval between the first sequence docetaxel chemotherapy and docetaxel rechallenge (> 6 months vs. ≤6 months) was independent predictor for PSA PFS. Response of docetaxel rechallenge (partial vs. no partial) was independent predictor for Rechallenge PSA PFS. mCRPC baseline serum-PSA and response of docetaxel rechallenge (partial vs. no partial) were independent predictors for OS. Conclusion These results further support the favorable profile of docetaxel rechallenge in mCRPC patients who were effectively treated with first-line docetaxel.